Editorial: Volume 3, Issue 1 - Kristy Archuleta; John Grable (Journal of Financial Therapy, 2012)
We made it! This simple statement not only describes the completion of this issue, but also the development and growth of the Journal of Financial Therapy.
Keywords: financial therapy